2006
DOI: 10.1111/j.1399-543x.2006.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and circadian variations in type 1 diabetes mellitus

Abstract: Diabetic autonomic neuropathy (DAN) commonly complicates diabetes and is associated with increased mortality rates over 5 yr. This fact denotes the significance of DAN prevention, mainly with effective glycemic control. However, total prevention of autonomic neuropathy in diabetic patients is not achievable. Thus, the timely detection of DAN and the use of effective means to improve autonomic nervous system function or slow down its progression become of utmost significance. Heart rate variability (HRV) is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
42
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 14 publications
12
42
0
3
Order By: Relevance
“…As there could be no comparable augmentation of adrenergic tone in isolated myocytes, underlying contractile depression was uncovered in the cell preparation. Chronic increased cardiac adrenergic tone is also present in type 1 diabetic patients [37,38] and this can account for the reduced adrenergic responsiveness of diabetic hearts. Elevated sympathetic tone might also contribute to the gradual development of diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…As there could be no comparable augmentation of adrenergic tone in isolated myocytes, underlying contractile depression was uncovered in the cell preparation. Chronic increased cardiac adrenergic tone is also present in type 1 diabetic patients [37,38] and this can account for the reduced adrenergic responsiveness of diabetic hearts. Elevated sympathetic tone might also contribute to the gradual development of diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have shown that spectral power in the HF range of HRV reflects parasympathetic activity (2,42); however, the interpretation of the LF range is controversial (2,42,44). Diabetes in humans is associated with a reduction in HRV (24,31,35), which is thought to be detrimental to cardiovascular health. In rats, there is evidence for a reduction in HRV and its HF component in association with insulin-deficient diabetes (19,28).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was observed in healthy subjects. In elderly patients circadian HRV variation is disturbed for example in arterial hypertension (HA) or diabetes mellitus (DM) [20,24,25].…”
Section: Discussionmentioning
confidence: 99%